Annual Migration of Monsoon Over Indonesia Maritime Continent Based on OLR Data - Yulihastin, Erma; Hermawan, Eddy (Teknologi Indonesia, 2012)
Annual migration of monsoon over Indonesia Maritime Continent (IMC) were analysed by Outgoing Longwave Radiation (OLR) data. Global climatology of NCEP/NCAR Reanalysis II (National Center for EnvironmentalPrediction/National Center for Atmospheric Research) namely OLR, wind, and precipitable water were derived from 1975 to 2010 which have 2,5o spatial degree resolution. The results showed those the annual migration were described by annual cycle of OLR<220 W/m2 occurred almost over IMC related to the wet periods (DJF). Whereas, OLR>240 W/m2 occurred only over south of IMC (3-9o S) related to the dry periods (JJA). Zonal variation of OLR showed annual cycle occured in areas of 2-10oS and 5-10oN, respectively. On the other hand, meridional variation described annual cycle in areas 90-120o E and 90-150, which respectively mentioned as area I and area II. Annual cycle of OLR in area I was symmetry with area II. Also, in areas I and II, parameters of OLR and precipitable waterwere symmetry each other. Signifi cants anticorrelation between OLR and precipitable water were -0.89 and -0.95 in area I and II, respectively.